EVALUASI AWAL UNTUK PERILAKU PUSTAKAWAN REFERENSI MELALUI CHAT PERPUSTAKAAN NASIONAL RI - Arief Wicaksono (Maktabatuna, 2020)
The National Library of Indonesia’s chat reference services was run for two months on May 16, 2020. Reference librarians who become chat administrators did not get special debriefing. They got only reading material that is related with virtual reference services. The initial evaluation of the chat reference librarian would be done. The evaluation was use the Reference Behavior Performance Guide and Information Service Providers from the Reference and User Services Association. The purpose of the evaluation is to obtain best practices. This research was use content analysis methods with qualitative perspective. The sample was selected with the specified criteria in order to obtain a transaction reference transcript which is assumed to be obtained aspect of behavior that desired. The findings found best practices from every aspect of the evaluation of reference librarians.